The “Labeled” Side of COVID-19 in India: Psychosocial Perspectives on Islamophobia During the Pandemic - Ahuja, Kanika K.; Banerjee, Debanjan (Frontiers in Psychiatry, 2021)
The Coronavirus disease 2019 (COVID-19) has emerged as a global public health threat over the last few months. Historically, infectious disease outbreaks like the plague, Influenza, cholera, HIV, etc. have generated stigma, prejudice, ‘othering’ and xenophobia, against certain communities. One such prevalent form of xenophobia, is Islamophobia or ‘fear and discrimination against the Muslims’. Though debated over its various facets and definitions, it is on the rise worldwide. India, being a socio-politically diverse and populous nation, has been facing unique challenges during COVID-19. Considering Hinduism and Islam are the two major religious communities, the subcontinent has witnessed complex dynamics in their relationship throughout history. The pandemic has further instigated xenophobia against the Muslims, and consequent discrimination, as well as unrest. This can have significant effect of public behaviour and health. In the recent past, few legislations in India were interpreted to be Islamophobic and generated nation-wide protest, which provided a fertile backdrop against the discriminative effects of the pandemic. Keeping this in background, this commentary highlights the social contexts of increase in Islamophobia in India during the pandemic, discusses the possible psychological explanations and public health impact, as well as outlines some ways to mitigate it focusing on collectivism.